2022
DOI: 10.3390/pharmaceutics14030577
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Sericin Hydrogel to Deliver Anthocyanins from Purple Waxy Corn Cob (Zea mays L.) Extract and In Vitro Evaluation of Anti-Inflammatory Effects

Abstract: Sericin-alginate hydrogel formulations with purple waxy corn (Zea mays L.) cob extract (PWCC) for topical anti-inflammatory application are developed and evaluated. The physical properties such as viscosity, pH, and anthocyanin release are examined and in vitro anti-inflammatory activities, such as NO inhibition and IL-6, IL-1β, TNF-α, iNOS, and COX-2 expression, are evaluated in LPS-stimulated RAW 264.7 murine macrophages. The sericin-alginate hydrogel is prepared by physical crosslinking through the ionic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 43 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…The swelling capacity (% Swelling) over 48 h of each hydrogel formulation containing alginate (S2, S4, S6), was higher than its respective formulation without alginate (S1, S3, S5) ( Figure 1 ). Swelling allows for the more rapid diffusion of anthocyanins from the hydrogel since the diffusion release mechanism occurs at the outer surface of the polymer, rather than the core porous structure [ 13 ]. Previous research reported that the kinetics release of hydrogels was achieved using the Korsmeyer–Peppas model, due to the electrostatic and H-bonding interactions between alginate, anthocyanin, and sericin in the hydrogel, which was confirmed by FT-IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The swelling capacity (% Swelling) over 48 h of each hydrogel formulation containing alginate (S2, S4, S6), was higher than its respective formulation without alginate (S1, S3, S5) ( Figure 1 ). Swelling allows for the more rapid diffusion of anthocyanins from the hydrogel since the diffusion release mechanism occurs at the outer surface of the polymer, rather than the core porous structure [ 13 ]. Previous research reported that the kinetics release of hydrogels was achieved using the Korsmeyer–Peppas model, due to the electrostatic and H-bonding interactions between alginate, anthocyanin, and sericin in the hydrogel, which was confirmed by FT-IR spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research reported that the kinetics release of hydrogels was achieved using the Korsmeyer–Peppas model, due to the electrostatic and H-bonding interactions between alginate, anthocyanin, and sericin in the hydrogel, which was confirmed by FT-IR spectroscopy. The release of anthocyanins was by rapid diffusion at the outer surface of the polymers in the hydrogel for up to 4 h, followed by the gradual swelling until 48 h, due to the cross-linking interactions between anthocyanins and the hydrophobic polymers [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations